CuInS2 Quantum Dot and Polydimethylsiloxane Nanocomposites for All‐Optical Ultrasound and Photoacoustic Imaging. Issue 20 (16th September 2021) - Bodian, Semyon; Colchester, Richard J.; Macdonald, Thomas J.; Ambroz, Filip; Briceno de Gutierrez, Martha; Mathews, Sunish J.; Fong, Yu Man Mandy; Maneas, Efthymios; Welsby, Kathryn A.; Gordon, Ross J.; Collier, Paul; Zhang, Edward Z.; et al.
Abstract: Dual‐modality imaging employing complementary modalities, such as all‐optical ultrasound and photoacoustic imaging, is emerging as a well‐suited technique for guiding minimally invasive surgical procedures. Quantum dots are a promising material for use in these dual‐modality imaging devices as they can provide wavelength‐selective optical absorption. The first quantum dot nanocomposite engineered for co‐registered laser‐generated ultrasound and photoacoustic imaging is presented. The nanocomposites developed, comprising CuInS2 quantum dots and medical‐grade polydimethylsiloxane (CIS‐PDMS), are applied onto the distal ends of miniature optical fibers. The films exhibit wavelength‐selective optical properties, with high optical absorption (> 90%) at 532 nm for ultrasound generation, and low optical absorption (< 5%) at near‐infrared wavelengths greater than 700 nm. Under pulsed laser irradiation, the CIS‐PDMS films generate ultrasound with pressures exceeding 3.5 MPa, with a corresponding bandwidth of 18 MHz. An ultrasound transducer is fabricated by pairing the coated optical fiber with a Fabry–Pérot (FP) fiber optic sensor. The wavelength‐selective nature of the film is exploited to enable co‐registered all‐optical ultrasound and photoacoustic imaging of an ink‐filled tube phantom. This work demonstrates the potential for quantum dots as wavelength‐selective absorbers for all‐optical ultrasound generation. Abstract : Bilayer nanocomposites comprising CuInS2 quantum dots within micron‐scale polydimethylsiloxane host layers are microfabricated with dip‐coating on the distal ends of optical fibers. The wavelength‐selective optical absorption (high from 400 to 600 nm; low from 700 to 1200 nm) is well‐suited to multimodality optical ultrasound and photoacoustic imaging of biological tissue structures such as atherosclerotic plaque.